2019
DOI: 10.1038/s41598-019-54693-y
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the adenosine salvage pathway and cyclic AMP modulation in oocyte energy metabolism

Abstract: A follicular spike in cyclic AMP (cAMP) and its subsequent degradation to AMP promotes oocyte maturation and ovulation. In vitro matured (IVM) oocytes do not receive the cAMP increase that occurs in vivo, and artificial elevation of cAMP in IVM cumulus-oocyte complexes improves oocyte developmental potential. This study examined whether mouse oocytes can use the cAMP degradation product AMP to generate ATP via the adenosine salvage pathway, and examined whether pharmacological elevation of cAMP in IVM cumulus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Hence, the study further corroborates the theory that cumulus cells provide metabolic support via gap junctional communication to maintain mitochondrial function and support oocyte meiotic progression and developmental competence. Consistent with our findings, Richani et al recently reported that the ATP levels increase in oocytes cultured with cumulus cells, and pharmacological inhibition of their gap-junction communication leads to a reduction of ATP levels in the oocytes [ 49 ]. These results demonstrate that the metabolic cooperativity between cumulus cells and oocytes mediated via gap junction communication directly affects intra-oocyte ATP levels.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the study further corroborates the theory that cumulus cells provide metabolic support via gap junctional communication to maintain mitochondrial function and support oocyte meiotic progression and developmental competence. Consistent with our findings, Richani et al recently reported that the ATP levels increase in oocytes cultured with cumulus cells, and pharmacological inhibition of their gap-junction communication leads to a reduction of ATP levels in the oocytes [ 49 ]. These results demonstrate that the metabolic cooperativity between cumulus cells and oocytes mediated via gap junction communication directly affects intra-oocyte ATP levels.…”
Section: Discussionsupporting
confidence: 93%
“…This might be attributed to the significant capability of forskolin for increasing the expression of embryo quality genes such as Mvh , Gdf9 , Scp3 and Rec8 expressions related to the unsupplemented group (Bahmanpour et al., 2020). The feat of using forskolin/IBMX meaningfully improved embryo development and has been evidenced in different animals (Gilchrist et al., 2015; Richani et al., 2019). Supplementation with 5.0 μM forskolin (54.7%) to in vitro culture medium had higher blastocyst rate compared with control group (44.9%) (Meneghel et al., 2017).…”
Section: Impacts Of Forskolin On In Vitro Embryo Developmentmentioning
confidence: 99%
“…For this fact, many studies have used in culture media to decrease lipid content by chemical lipolysis, and enhance the cryotolerance and post‐vitrification quality of embryos (Bilodeau‐Goeseels, 2011; Paschoal et al., 2014, 2016; Zeng et al., 2014). Thus, forskolin increases the intracellular concentrations of cAMP, which inhibits the immediate resumption of meiosis and gives the oocyte more time to gain optimal developmental competence (Costa et al., 2019; Razza, 2018; Richani et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The ADO salvage pathway involves two steps: First, AMP is phosphorylated to ADP and then ADP to ATP, this might be an alternative pathway for ATP production to satisfy the energetic demands in the meiotic maturation of the oocyte, therefore the ADO salvage pathway has to be active in order to take advantage of the large amount of AMP generated by phosphodiesterase breakdown of cAMP [ 81 , 82 ]. In fact, it has been found that ATP is generated from AMP through the adenosine salvage pathway in mouse oocytes, and that the increment in the cAMP levels modifies adenine nucleotide metabolism, providing the AMP required for energy production through this salvage pathway [ 83 ].…”
Section: Ado Metabolismmentioning
confidence: 99%